Factors predicting 31-year survival among a population cohort in Northern Finland. Issue 1 (1st January 2021) - Perkkiö, Yrjö; Auvinen, Juha; Timonen, Markku; Jokelainen, Jari; Valkeapää, Nihkolas; Koiranen, Markku; Saltevo, Juha; Keinänen-Kiukaanniemi, Sirkka
ABSTRACT: We evaluated the survival of a subarctic population and the significance of traditional risk factors for mortality, causes of death and their seasonal variation from the period of 1984–2014. By the end of 2014 (follow-up), 644 (34.4% from 1, 869) participants had died (42.1% of cardiovascular causes, 22.4% of neoplastic diseases). The average age at death±SD was 74.6±11.4 years for women (n=284) and 70.2±12.0 years for men (n=360). After adjusting for baseline age, the major risk factors predicting death were male sex (hazard ratio [HR] 1.80; 95% confidence interval [CI] 1.54–2.10), current smoking (HR 1.85; 95% CI 1.58–2.17), obesity (HR 1.75; 95% CI 1.45–2.12), high blood pressure (HR 1.46; 95% CI 1.24–1.72), cardiovascular disease (HR 1.62; 95% CI 1.36–1.93) and depression (HR 1.61; 95% CI 1.21–2.14) at baseline. The most common causes of death and the main risk factors predicting death in this population were the same as reported globally. Lifestyle factors had an important impact in predicting survival. The most common causes of death were the same for men and women. There was no significant difference in overall mortality rate between winter and summer, but cerebrovascular and pulmonary causes of death were more common during winter.